2023
DOI: 10.1111/ijlh.14034
|View full text |Cite
|
Sign up to set email alerts
|

An NGS based MRD evaluation from acute myeloid leukemia patients

Abstract: Introduction: Measurable residual disease (MRD) is a prognostic factor for acute myeloid leukemia (AML). A next-generation sequencing (NGS) based MRD panel was developed and the results were validated. Methods:The NGS sequencing data was collected from 1003 Chinese AML patients. Results:The sequencing data from 586 newly diagnosed AML patients showed that NRAS mutation was most common (20.8%), followed by NPM1 (19.4%), FLT3-ITD (18.5%), and DNMT3A (15.4%). NPM1 and FLT3-ITD mutations were less in Chinese than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Therefore, inhibiting tumor angiogenesis and blocking the nutrient supply for angiogenesis has become a new opportunity for treatment[ 26 ]. Chen et al [ 27 ] showed that leukemia cells in patients with AML can autonomously secrete VEGF. After combining with VEGFR, the cells promote micro-angiogenesis and cell proliferation in the body, creating a pathway for leukemia cells to metastasize to other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibiting tumor angiogenesis and blocking the nutrient supply for angiogenesis has become a new opportunity for treatment[ 26 ]. Chen et al [ 27 ] showed that leukemia cells in patients with AML can autonomously secrete VEGF. After combining with VEGFR, the cells promote micro-angiogenesis and cell proliferation in the body, creating a pathway for leukemia cells to metastasize to other organs.…”
Section: Discussionmentioning
confidence: 99%
“…23 Panel should also exclude mutations consistent with premalignant clonal hematopoiesis (eg, DNMT3A, TET2, ASXL1). 68 Few studies conducted to study tailored post remission approach using MRD showed positive outcome, 69,70 but further information from prospective trials is still needed.…”
Section: Aml Mrdmentioning
confidence: 99%